Hereditary motor and sensory neuropathy, caused by mutations in the NEFL gene in a family from Karachaevo-Cherkessia - E. L. Dadali; A. Kh.-M. Маkаоv; V. A. Galkina; F. A. Konovalov; A. V. Polyakov; M. V. Bulakh; R. A. Zinchеnkо (Нервно-мышечные болезни)
The clinical and genetic features of hereditary motor and sensory neuropathy (HMSN; Charcot–Marie–Tooth disease, CMT) caused by newly identified missense mutation s.65G>T (p.Pro22His) in NEFL gene located on the chromosome 8р21.2 are described. The disease was diagnosed in a large family from Ust-Dzhegutinsky district of the Karachay-Cherkess Republic with the segregation of the disease in four generations. The prevalence of the HMSN in that district was found to be 1:4340 persons, including 1:3376 among Karachays. The clinical picture of the disease was characterized by onset at the age of 11–14 years, weakness in foot muscles and steppage gait. The specific features in the majority of patients were the absence of major sensory disturbances, as well as long-term preserved distal arm muscles. Nerve conduction velocity in the median nerve varied from 30 to 42 m/s, which corresponds to values in patients with CMT2E, previously described.